Local Oral Health Programs Support Public Health Infrastructure, Dental Providers and the Public During the COVID-19 Pandemic - Mary E. Foley; Shakalpi Pendurkar (Taylor & Francis Group, 2023)
ABSTRACTBackground The Dental Public Health workforce is made up of highly versatile, well-educated and qualified professionals ready to act and assist in times of crises. In early 2020, the COVID-19 pandemic emerged across the globe, creating havoc for public health officials, oral health providers, and the public. The need for trained staff to support pandemic efforts was critical.Methods In California, personnel from local oral health programs (LOHPs) were summoned to support community pandemic efforts.Results California local public health departments had the oral health infrastructure and capacity to assist in pandemic containment efforts as well as community oral health support efforts. These included COVID-19 contact tracing, testing, administrative support,administering vaccines, and supporting local dental providers.Practical Implications Having adequate LOHP staff in place to support public health infrastructure, the dental workforce and the public essential as this pandemic winds down and the ongoing risk of new variants and/or disease exist.